JURIDICAL REVIEW OF THE JUDGE'S CONSIDERATION OF NOT ACCEPTING THE BANKRUPTCY APPLICATION AGAINST - Sopian, Singgih; Abas, Muhamad; Lubis, Adyan (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Based on the problem of bankruptcy and the postponement of debt payment obligations where PT. Fuji Smbe Indonesia filed a Bankruptcy Application against PT. Amanda Gumulung Sejahtera is due to her inability to pay her debts that have matured or the Suspension of Debt Payment Obligations (PKPU), in this case what is the legal basis for the judge's consideration of not accepting the bankruptcy application against Pt. Amanda Gumulung Sejahtera and the legal consequences for the debtor for the delay in debt payment obligations. The purpose of writing is to find out the legal basis for the judge's consideration of not accepting the bankruptcy application and the legal consequences for the debtor for the delay in debt payment obligations. This research uses a normative legal approach method or library legal research which is carried out by researching literature materials. Data sources consist of secondary data including primary, secondary and tertiary legal materials. The conclusion is that PT. Amanda Gumulung Sejahtera has met the bankruptcy requirements, namely having more than one creditor and the existence of duet and collectible debts that have been regulated in Law Number 37 of 2004 concerning the Postponement of Debt Payment Obligations.